Optimalisasi Potensi Wirausaha Mahasiswa Melalui Pendampingan Bisnis P2MW “Ampena Kerupuk Amplang” Untuk Meningkatkan Keterampilan Berwirausaha - Suhab, Resky Faradibah (STIE Amkop Makassar, Indonesia, 2025)
The Student Entrepreneurship Development Program (P2MW) is an initiative designed to develop students' entrepreneurial potential through intensive mentoring and training, covering various important aspects of the business world. This study aims to evaluate the success of the mentoring provided to Ampena Kerupuk Amplang, a student-owned business, in improving their entrepreneurial skills. The main focus of the P2MW program is to enhance students' abilities in business planning, financial management, digital marketing, and product development. The mentoring method involves structured guidance, including technical training and business consultations, to help students understand and implement effective strategies in running their businesses. The results of the study show that with intensive mentoring and organized incubation, students experienced significant improvement in their entrepreneurial skills, as reflected in the enhanced product quality and their ability to manage marketing efforts. Furthermore, students were able to utilize digital marketing more effectively to introduce their products to a wider market, which in turn contributed to an increase in sales and overall business success. Therefore, this study demonstrates that the P2MW program, through structured mentoring, has a positive impact on enhancing students' entrepreneurial competencies and the sustainability of their businesses.